THE CORRELATION BETWEEN STUDENTS’ ANXIETY AND LEARNING MOTIVATION TOWARDS STUDENTS’ SPEAKING SKILL - Amar Hamzah Farosy; Dedi Sumarsono; Baiq Sumarni (The Center for Language Development, Mataram State Islamic University., 2019)
This study aims to determine the correlation between students’ anxiety and learning motivation towards students speaking skill at SMPN 19 Mataram. This research is a quantitative, counting the data used multiple correlation . The sample of this study consisted of 44 students; the instrument used in this study was an oral test and questionnaires that belongs to anxiety and motivation. Data analysis technique is multiple correlation. The findings of the study showed that the r-test was 0.618 and 0.624. This showed that the alternative hypothesis (Ha) is accepted and as average score is high, Then the result in F- table shows that Fh>ft (21,81375>3,22). From the findings of this study, it is recommended that teachers can fixed students’ anxiety and teachers build the motivations students in teaching speaking skill.